The men who weren't even there: Legislative voting with absentees - László Á. Kóczy; Péter Miklós Pintér (Hungarian Academy of Sciences, Institute of Economics, 2011)
Voting power in voting situations is measured by the probability of changing decisions by altering the cast 'yes' or 'no' votes. Recently this analysis has been extended by strategic abstention. Abstention, just as 'yes' or 'no' votes can change decisions. This theory is often applied to weighted voting situations, where voters can cast multiple votes. Measuring the power of a party in a national assembly seems to fit this model, but in fact its power comprises of votes of individual representatives each having a single vote. These representatives may vote yes or no, or may abstain, but in some cases they are not even there to vote. We look at absentees not due to a conscious decision, but due to illness, for instance. Formally voters will be absent, say, ill, with a certain probability and only present otherwise. As in general not all voters will be present, a thin majority may quickly melt away making a coalition that is winning in theory a losing one in practice. A simple model allows us to differentiate between winning and more winning and losing and less losing coalitions reected by a voting game that is not any more simple. We use data from Scotland, Hungary and a number of other countries both to illustrate the relation of theoretical and effective power and show our results working in the practice.
Keywords: C71; D72; 330; a priori voting power; power index; being absent from voting; minority; Shapley-Shubik index; Shapley value; Abstimmung; Wahlverhalten; Wahlbeteiligung; Abstimmungsspiel; Shapley-Wert; Welt